An investigation into the synergistic action of chemotherapy and photodynamic therapy in resistant skin cancers - Nsole Biteghe, Fleury Augustin (Department of Human Biology, 2015)
Melanoma is a form of skin cancer, arising from epidermal cells of the melanocyte lineage, which undergo a series of transformations and genetic alterations that may give rise to both pigmented and unpigmented melanoma. Melanoma represents 4% of all skin cancers but due to its aggressive nature, it accounts for 80% of death among skin cancer patients. South Africa has a melanoma incidence rate that is second worldwide to only Australia. In melanoma; non-metastatic primary tumours are treated by surgical resection. However, metastatic melanoma is highly resistant to conventional radio and chemotherapy, thus reducing the median life of patient's diagnosis with the metastatic form to about 7-9months. Given the implications of the pigment in failure of chemotherapy, two human metastatic pigmented and unpigmented melanoma cell lines were used to investigate the mechanisms underlying chemo-resistance. During the course of this study, the first aim was to determine the concentration of the chemotherapeutic drug dacarbazine (DTIC) causing fifty percent decrease in melanoma cell viability (LD50), then to investigate the possible synergism of hypericin activated-photodynamic therapy in reducing (HYP-PDT) melanoma cell viability, when combined with chemotherapy. In addition we wanted to assess the morphology and the clonogenic capacity of the melanoma cells, after the different treatments and further investigate the ATP-binding cassette (ABC) transporters (ABCB5/1 & ABCG2) expression profile, before and after chemotherapeutic (DTIC) and combination therapy (DTIC+HYP-PDT) treatments.